Evaluations of cooling exercised muscle with MR imaging and 31P MR spectroscopy - Yanagisawa, O.; Niitsu, M.; Takahashi, H.; Goto, K.; Itai, Y. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: To investigate the effects of cooling human skeletal muscle after strenuous exercise using 31P MR spectroscopy and MR imaging. METHODS: 14 male subjects (mean age +/- SD, 23.8 +/- 2.3 yr) were randomly assigned to the normal (N = 7) or the cooling group (N = 7). All subjects performed the ankle plantar flexion exercise (12 repetitions, 5 sets). Localized 31P-spectra were collected from the medial gastrocnemius before and after exercise (immediately, 30, 60 min, 24, 48, 96, and 168 h) to determine the ratio of inorganic phosphate to phosphocreatine (Pi/PCr) and intracellular pH. Transaxial T2-weighted MR images of the medial gastrocnemius were obtained to calculate T2 relaxation time (T2), indicative of intramuscular water level, before and after exercise (24, 48, 96, and 168 h). In addition, the muscle soreness level was assessed at the same time as 31P-spectra measurements. Fifteen-minute cold-water immersion was administered to the cooling group after exercise and initial postexercise measurements. RESULTS: The control group showed significantly increased T2 from rest at 48 h after exercise (P < 0.05), but the cooling group showed no significant change in T2 throughout this study. Both groups showed a significantly decreased intracellular pH immediately after exercise (P < 0.05). After that, the cooling group showed a significantly greater value than the value at rest or the control group at 60 min after exercise (P < 0.05). For the Pi/PCr, no significant change was observed in both groups throughout this study. The muscle soreness level significantly increased immediately and at 24-48 h after exercise in both groups (P < 0.05). CONCLUSION: The findings of this study suggest that cooling causes an increase in intracellular pH and prevents the delayed muscle edema.